2014
DOI: 10.1016/j.scitotenv.2013.12.059
|View full text |Cite
|
Sign up to set email alerts
|

Multi-isotope (carbon and chlorine) analysis for fingerprinting and site characterization at a fractured bedrock aquifer contaminated by chlorinated ethenes

Abstract: The use of compound specific multi-isotope approach (C and Cl) in the characterization of a chlorinated ethenes contaminated fractured aquifer allows the identification of several sources and contaminant plumes, as well as the occurrence of biodegradation and mixing processes. The study site is located in Spain with contamination resulting in groundwater concentrations of up to 50mg/L of trichloroethene (TCE), the most abundant chlorinated ethene, and 7 mg/L of tetrachloroethene (PCE). The potential sources of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
31
1
2

Year Published

2014
2014
2020
2020

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 50 publications
(36 citation statements)
references
References 40 publications
2
31
1
2
Order By: Relevance
“…These data suggest a lower extent of degradation for both compounds downstream. CMs moving downstream in the pit source's influence area might inhibit chlorinated ethenes biodegradation (Bagley et al, 2000), explaining the results previously reported by Palau et al (2014).…”
supporting
confidence: 72%
See 3 more Smart Citations
“…These data suggest a lower extent of degradation for both compounds downstream. CMs moving downstream in the pit source's influence area might inhibit chlorinated ethenes biodegradation (Bagley et al, 2000), explaining the results previously reported by Palau et al (2014).…”
supporting
confidence: 72%
“…The CT content decreased by nearly one order of magnitude between Mar-10 and Nov-14 and DCM and CS 2 were always b0.2 μM (Table A3). Table 1 CT, CF and DCM carbon isotopic composition (δ 13 C, ‰) of the three Òdena site's pollution sources previously identified by Palau et al (2014) are shown. Samples from the abandoned barrels, the tank and the pit were taken from 2002 to 2005. δ 13 C ranges of commercial CMs from different suppliers (see Table A2 in SI for details) are also shown.…”
Section: Pit Source's Influence Areamentioning
confidence: 99%
See 2 more Smart Citations
“…To overcome the high degree of uncertainty when using the molar fraction for SA purposes, an analysis was conducted on the basis of δ 13 C sum . As several contaminants were detected at the site and potential biodegradation can be hypothesized from the molar fraction distribution (Figure 2), the approach presented made use of the isotope balance δ 13 C sum rather than considering the isotopic signature of specific compounds (Table 1) [13,30]. Yet, if contaminants undergo a preferential transport along the plumes and/or when biodegradation processes are taking place, the δ 13 C sum interpretation is not an easy task [31].…”
Section: Source Apportionmentmentioning
confidence: 99%